Simplify 4t^2- 16/8/t - 2/6
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,551 answers
starTop subjects are Math, Science, and Business
WE have to simplify [(4t^2-16) / 8] / [(t-2) / 6]
[(4t^2-16) / 8] / [(t-2) / 6]
=> [(4t^2-16) / 8] * [6 / (t-2)]
=> [(4t^2-16)*6 / 8*(t-2)]
=> [(2t - 4)(2t + 4)*6 / 8*(t-2)]
=>[4(t - 2)(t + 2)*6 / 8*(t-2)]
=> [(t - 2)(t + 2)*3 / (t-2)]
=> [(t + 2)*3 ]
=> 3t + 6
Therefore [(4t^2-16) / 8] / [(t-2) / 6] = 3t + 6
Related Questions
- Simplify the expression: `((4t)^-2*t^0)/(t^6*v^-8)`
- 1 Educator Answer
- `int (dt)/(t^2 sqrt(t^2 - 16))` Evaluate the integral
- 2 Educator Answers
- Simplify (x-2)^2
- 1 Educator Answer
- `a(t) = t^2 - 4t + 6, s(0) = 0, s(1) = 20` A particle is moving with the given data. Find...
- 1 Educator Answer
- Combine like terms and simplify: 12t^6-t^3+8t^6+4t^3-t^7-3t^3
- 1 Educator Answer
To simplify 4t^2-16/8/t -6.
4t^2- 2/t - 6.
The secod term 16/2/t is treated as (16/8)/t = 8/t, as there are two divisions with out brackets. Divisions are of equal priority. Therefore 16/2 is the first division. So the priority is for 16/2.
Therefore 4t^2 -16/8/t - 6 = 4t^2-8/t - 6 which is in the simplest form.
First, we'll re-write the term 16/8/t, the denominator 8 coming down near the denominator t:
16/8/t = 16/8t
We'll divide by 8 both numerator and denominator:
16/8t = 2/t
Now, we'll simplify by 2 the term 2/6:
2/6 = 1/3
We'll re-write the given expression in a simplified manner:
4t^2 - 2/t - 1/3
Student Answers